2015
DOI: 10.1002/adma.201502536
|View full text |Cite
|
Sign up to set email alerts
|

Guided Photoluminescence from Integrated Carbon‐Nanotube‐Based Optical Waveguides

Abstract: Thin films and ridge waveguides based on large-diameter semiconducting single-wall carbon nanotubes (s-SWCNTs) dispersed in a polyfluorene derivative are fabricated and optically characterized. Ridge waveguides are designed with appropriate dimensions for single-mode propagation at 1550 nm. Using multimode ridge waveguides, guided s-SWCNT photoluminescence is demonstrated for the first time in the near-infrared telecommunications window.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…[179] Guided propagation and detection of telecom wavelengths signals have also been demonstrated. [179,180] However, other important factors for practical SWCNT-optical interconnects remain largely unexplored including reproducibility, tight modal confinement, and high-density integration of multiple input and output photonic channels.…”
Section: Chirality-enriched Swcnt Optoelectronic Integrated Circuitsmentioning
confidence: 99%
See 1 more Smart Citation
“…[179] Guided propagation and detection of telecom wavelengths signals have also been demonstrated. [179,180] However, other important factors for practical SWCNT-optical interconnects remain largely unexplored including reproducibility, tight modal confinement, and high-density integration of multiple input and output photonic channels.…”
Section: Chirality-enriched Swcnt Optoelectronic Integrated Circuitsmentioning
confidence: 99%
“…In another study using a similar waveguide‐SWCNT integration scheme, few‐chirality SWCNTs were found to have diameter‐dependent photocurrent generation properties, such that large diameter SWCNTs only contribute to photocurrent generation when the waveguide is photoexcited 179. Guided propagation and detection of telecom wavelengths signals have also been demonstrated 179,180. However, other important factors for practical SWCNT‐optical interconnects remain largely unexplored including reproducibility, tight modal confinement, and high‐density integration of multiple input and output photonic channels.…”
Section: Computing Applications Of Chirality‐enriched Swcntsmentioning
confidence: 99%
“…This can be attributed to their relatively low quantum efficiency and their high sensitivity to the surrounding environment . The massive progress made in purification technologies of SWCNTs, however, has recently increased their potential in light emitter devices …”
Section: Transistorsmentioning
confidence: 99%
“…Since their discovery in the early nineties, single wall carbon nanotubes (SWNTs) have attracted great attention due to their potential for nanoscale electronics, sensors, photodetectors, solar cells, LEDs, and, more recently, photonics . Carbon nanotubes are characterized by ballistic transport (at low bias and within hundreds of nm) and single wall carbon nanotube field effect transistors (SWNT‐FETs) can have extremely high I ON / I OFF ratios .…”
Section: Introductionmentioning
confidence: 99%